Plasma-to-tumour tissue integrated proteomics using nano-omics for biomarker discovery in glioblastoma - Xinming Liu; Hanan Abmanhal-Masarweh; Olivia Iwanowytsch; Emmanuel Okwelogu; Kiana Arashvand; Konstantina Karabatsou; Pietro Ivo D’Urso; Federico Roncaroli; Kostas Kostarelos; Thomas Kisby; Marilena Hadjidemetriou (Nature Communications)
Abstract Glioblastoma (GB) is the most lethal brain cancer, with patient survival rates remaining largely unchanged over the past two decades. Here, we introduce the Nano-omics integrative workflow that links systemic (plasma) and localised (tumour tissue) protein changes associated with GB progression. Mass spectrometry analysis of the nanoparticle biomolecule corona in GL261-bearing mice at different stages of GB revealed plasma protein alterations, even at low tumour burden, with over 30% overlap between GB-specific plasma and tumour tissue proteomes. Analysis of matched plasma and surgically resected tumour samples from high-grade glioma patients demonstrates the clinical applicability of the Nano-omics pipeline. Cross-species correlation identified 48 potential GB biomarker candidates involved in actin cytoskeleton organisation, focal adhesion, platelet activation, leukocyte migration, amino acid biosynthesis, carbon metabolism, and phagosome pathways. The Nano-omics approach holds promise for the discovery of early detection and disease monitoring biomarkers of central nervous system conditions, paving the way for subsequent clinical validation.